Ketidaksantunan Berbahasa Indonesia Dalam Interaksi Sosial Tayangan Rakyat Bersuara Inews TV - Machfudhotus Sa’Adah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the forms, strategies, and functions of linguistic impoliteness in the Indonesian public discussion program Rakyat Bersuara, employing a sociopragmatic approach. The study is motivated by the prevalence of impolite utterances in public discussions. A descriptive-qualitative method was used. The data consist of utterances containing impoliteness from the Rakyat Bersuara program, collected through listening and note-taking techniques and subsequently analyzed qualitatively. The analysis draws upon theories regarding forms of impoliteness (synthesized from five experts), Culpeper’s strategies and functions of impoliteness, and a sociopragmatic framework. The results reveal five forms of impoliteness: recklessness, face-playing, face-belittling, threatening, and face-destroying. Additionally, four impoliteness strategies were identified: bald-on-record impoliteness, positive impoliteness, negative impoliteness, and withholding politeness. The functions of impoliteness identified include affective, coercive, and entertaining functions. From a sociopragmatic perspective, the use of impoliteness in public discussions is influenced by various social factors, such as the social relationship between speakers and interlocutors, differing viewpoints, efforts to maintain self-image, power relations, communication norms, and the presence of an audience. This study is expected to raise public awareness regarding the importance of using polite language when expressing opinions, particularly in the public sphere.
Validasi dan Finalisasi Ratna 12 Agustus 2026
Keywords: Ketidaksantunan Berbahasa; Sosiopragmatik; Culpeper